GOVERNANCE OF THE 2024 PRESIDENTIAL AND VICE-PRESIDENTIAL ELECTIONS IN TANGERANG CLASS IIA YOUTH CORRECTIONAL FACILITY - Ramadhan, Faris Abiyyu (Universitas Nusa Cendana, 2025)
General elections are a form of the people's sovereign rights in using a democratic system to provide voting rights in electing the president and vice president. This right is also held by Prisoners (WBP), so a forum is needed to implement this right. The General Election Commission (KPU) has the authority to organize it in accordance with Law Number 7 of 2017 concerning General Elections and Correctional Institutions (Lapas) in this case, namely the Tangerang Class IIA Youth Correctional Institution, which is involved in organizing general elections to provide facilities for WBP to exercise their voting rights. Polling stations (TPS) specially made in prisons are called special TPS. In their implementation, governance is needed so that they can run smoothly, structured and in accordance with applicable laws and regulations. This study examines the authority of the KPU and prisons in organizing the 2024 Presidential and Vice Presidential Elections and the application of governance principles in organizing the 2024 Presidential and Vice Presidential Elections at the Tangerang Class IIA Youth Correctional Institution. This research is qualitative research with a case study approach and literature study related to legal norms. The results of this study explain the implementation of the governance of the 2024 presidential and vice presidential elections at the Tangerang Class IIA Youth Penitentiary in accordance with the authority of the KPU and Lapas. Basically, the implementation went well, but there were several suggestions and innovations from the author to provide encouragement for future progress. Keywords: Election; Correctional Inmates (WBP); Special Polling Station